Inhibitory and Anti-Biofilm Effects of Orthoshipon aristatus Against Candida albicans - Rahmasari, Ratika; Chairunissa, Ananda Hanny; Irianti, Marina Ika; Forestrania, Roshamur Cahyan; Arifianti, Ayun Erwina; Suryadi, Herman; Makau, Juliann Nzembi; Jantan, Ibrahim; Elya, Berna (Pharmaceutical Sciences and Research, 2020)
There are increasing number of reports on Candida albicans developing resistance to available anti-fungal drugs. Thus, there is an urgent need to discover new agents for treatment of candidiasis. The alcoholic extracts of Orthoshipon aristatus have been shown to exhibit antifungal activity against C. albicans by using the agar diffusion and broth microdilution methods. However, the underlying mechanisms of anti-C. albicans effect of O. aristatus have not been well understood. This study was aimed to evaluate the cytotoxic and anti-biofilm effects of the n-hexane and ethanol extracts of purple and white varieties of O. aristatus leaves and branches against C. albicans. The effect of n-hexane and ethanol extract against C. albicans growth was carried out by crystal violet viability assay. IC50 values of the most active extract, and nystatin and fluconazole as positive controls were also determined by the crystal violet assay. Evaluation of the anti-biofilm effect was performed by treating C. albicans with the extracts at adhesion, development, and biofilm maturation stages using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The n-hexane extract of the purple variety of O. aristatus leaves demonstrated the strongest cytotoxic activity against C. albicans amongst the tested extracts, with an IC50 value of 0.67 µg/mL. The extract also showed strong anti-biofilm effect as fluconazole, with pronounced inhibition at the adhesion stage and less activity at the biofilm development and maturation stages. These results suggested that the n-hexane extract of the purple variety of O. aristatus leaves could be explored for discovery and development of anti-C. albicans agent.